2019
DOI: 10.1002/ejsp.2608
|View full text |Cite
|
Sign up to set email alerts
|

Support for collective action against refugees: The role of national, European, and global identifications, and autochthony beliefs

Abstract: To understand recent anti‐refugee protests in Europe, we examined how different levels of inclusiveness of group identities (national, European, and global) are related to intentions to protest among native Europeans. We focused on the mediating role of autochthony (a belief that the first inhabitants of a territory are more entitled) and the moderating role of threat. Survey data from 11 European countries (N = 1,909) showed that national identification was positively associated with autochthony, and therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 69 publications
(114 reference statements)
4
42
0
1
Order By: Relevance
“…Threats experienced by residents are expanded beyond established threat types (symbolic, realistic) to include threats that are specific to the refugee context (e.g., safety threat, cohesion threat, altruistic threat; Landmann, Gaschler, & Rohmann, ). Residents’ willingness to participate in collective action against refugees is predicted by their autochthony beliefs, that is, their sense of entitlement to defend their homeland against the influx of refugees (Hasbún López et al., ). Refugee‐specific vulnerabilities are extracted from speeches by UK politicians and from UK newspaper articles (Goodman & Kirkwood, ).…”
Section: Discussionmentioning
confidence: 99%
“…Threats experienced by residents are expanded beyond established threat types (symbolic, realistic) to include threats that are specific to the refugee context (e.g., safety threat, cohesion threat, altruistic threat; Landmann, Gaschler, & Rohmann, ). Residents’ willingness to participate in collective action against refugees is predicted by their autochthony beliefs, that is, their sense of entitlement to defend their homeland against the influx of refugees (Hasbún López et al., ). Refugee‐specific vulnerabilities are extracted from speeches by UK politicians and from UK newspaper articles (Goodman & Kirkwood, ).…”
Section: Discussionmentioning
confidence: 99%
“…They may instead be motivated to preserve the system that promotes their advantage (Dovidio et al, 2009). Consequently, stronger identification with the advantaged group (and low perceptions of inequalities) may promote collective action to manifest or improve the status of the advantaged groups (Çakal et al, 2011;Çakal et al, 2016;Hasbún López et al, 2019;Selvanathan et al, 2018, Study 1;Thomas et al, 2019).…”
Section: Levels Of Categorizationmentioning
confidence: 99%
“…For example, a study of eleven European countries found that national identity was positively associated with protests against refugees (Hasbún López et al, 2019). Conversely, those who psychologically identify with the disadvantaged groups (e.g., common identity, dual identity, or opinion-based identity) should feel some sense of closeness with disadvantaged group members, which should promote solidarity (e.g., Reicher et al, 2006).…”
Section: Levels Of Categorizationmentioning
confidence: 99%
“…First, of course, the protests may indeed be directly about excluding certain groups, as many accounts of the anti-refugee (e.g., Hasbún López et al 2019), anti-Muslim (e.g., Pilkington 2016), or anti-gay (e.g., Gunther 2019) protests illustrate. Avery's account of protests protecting the neighborhood space from the "contamination" brought by the ultimate outcasts-prisoners and "mentally impaired accused" who lack adequate facilities while awaiting trial-is an example of a similar direct exclusion of a group of people.…”
Section: Th E Power To Change the Power To Excludementioning
confidence: 99%